(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2018)
Cancer is referred as uncontrolled growth of abnormal cell mass. Out of the several types of cancer, prostate cancer (PC) has become a major public health problem in men worldwide. Bcl-2 and p27 proteins are important regulatory molecules of cell cycle. Failure of cell cycle regulation leads to uncontrolled cell proliferation and causes cancer. For designing an effective structural based targeted drug, the assessment of protein-protein and protein-ligand interaction is indispensable. Therefore for treatment of PC, we selected a ribosome inactivating protein, Ricin, for assessment of its therapeutic nature. In the present work through CLUSTAL-W phylogenetic analysis, we found that Bcl-2 protein was found more conserved than p27. Further Bcl-2 was selected as target molecule for docking study with Ricin protein and other chemically synthetic inhibitor molecules i.e. 2-difluoromethylornithine (DFMO) and Sarcosine, as lead molecule. Through HEX5.1 docking software docking was performed between targeted receptor and lead molecules. Energy maximum (Emax= -93.12) and energy minimum (Emin= -163.07) was observed for docking complex of optimised and energy minimised structure of Bcl-2 receptor with Ricin, which in turn shows that it is highly stable interaction. On the other hand, for synthetic inhibitors, we found energy maximum (DFMO; Emax= -77.17, Emin= -117.83 and Sarcosine; Emax= -72.23, Emin= -103.00) and energy minimum, which are significant more as compared to Ricin docking complex. Due to ricin docking complex having less energies shows stable interaction with Bcl-2. We also observed that Ricin is less toxic (lesser log P value) as compared to other molecules by toxicity analysis by ADME/TOX server. These evidences show this Ricin could be better drug for PC. Further results are needed to validate by in vitro and in vivo study to make proper elucidation of drug for better PC treatment.